Constitutionalized But Not Constitute: The Case of Right to Social Security in Indonesia - Stefanus Hendrianto (The Constitutional Court of the Republic of Indonesia, 2020)
Previous studies on the development of socio-economic rights in Indonesia heavily focus on the Constitutional Court’s decisions in upholding the rights. But there is still minimum study on the political economy behind the development of socio-economic rights in Indonesia. This article will analyze the development of socio-economic rights through the lenses of the right to social security. This article relies on two major theoretical frameworks to analyze the development of the right to social security in Indonesia. The first theoretical framework is the authoritarian constitutionalism in the economic sphere. The second theoretical framework in this article is Kathrine Young’s theory of the construction of socio-economic rights. This article postulates that the rights to social security has been constitutionalized but not constituted in Indonesia for several reasons. First, and foremost, the legacy of authoritarian constitutionalism that prioritizing economic growth over the fulfilment of social economic rights. The “growth” ideology has contributed to the discrepancy between the constitution and reality, in which the government merely considers protection of socio-economic rights as extra cost, which will hamper the growth of the economy. Second, the lack of philosophical and comparative analysis in the interpretation of rights to social security. Third, the transformation of the Court as a detached court in the enforcement of the rights to social security. The element of detachment is clearly seen in the Court’s too much deferral to the Executive and Legislative branches in defining the scope and meaning of the right to social security. Finally, the failure of social movement to create a new narrative on injustice and the importance of rights to social security.